Efficacy and Safety of Vedolizumab for Induction of Remission in Inflammatory Bowel Disease—the Israeli Real-World Experience. Issue 3 (13th February 2017) - Kopylov, Uri; Ron, Yulia; Avni-Biron, Irit; Koslowsky, Benjamin; Waterman, Matti; Daher, Saleh; Ungar, Bella; Yanai, Henit; Maharshak, Nitsan; Ben-Bassat, Ofer; Lichtenstein, Lev; Bar-Gil Shitrit, Ariella; et al.
Abstract : Article first published online 13 February 2017. Abstract : Background: Vedolizumab (VDZ) is an anti-integrin monoclonal antibody effective in ulcerative colitis (UC) and Crohn's disease (CD). The aim of this study was to examine the "real world" efficacy and safety of VDZ in a large national patient cohort. Methods: Patients with inflammatory bowel disease treated with VDZ were prospectively followed for 14 weeks. Patients who completed the induction protocol (week 0/2/6/14) or discontinued the treatment before week 14 for adverse events (AEs) or primary nonresponse were included. The primary outcome was induction of clinical remission at week 14; secondary outcomes included clinical response and corticosteroid-free clinical remission. Results: A total of 204 patients (CD-130, UC-69, inflammatory bowel disease–unclassified-5) from 8 centers in Israel were included. Fifteen (7.4%) of the patients were anti–tumor necrosis factor naive and 46 (35.4%) had a previous surgery. For patients with CD, 69/130 (53.1%) responded to treatment; 45 (34.6%) achieved clinical remission; and 38 (29.2%) achieved corticosteroid-free remission at week 14. Fourteen (10.7%) patients discontinued VDZ before week 14 due to primary nonresponse or AEs. For UC, 32/74 (43.2%) responded to treatment; 20 (28.4%) achieved clinical remission, and 18 (24.3%) achieved corticosteroid-free remission at week 14. Fifteen (20.3%) patients with UC did not complete the induction due to primary nonresponse or AEs. AEs were reported by 29 (14.2%) patients (CD and UC combined), most common being nasopharyngitis and skin eruptions. Conclusions: In a large real-world Israeli cohort of anti–tumor necrosis factor–experienced patients with inflammatory bowel disease, VDZ was effective and safe in induction of clinical remission and steroid-free clinical remission.